Analytical shakedown, ratchetting and creep solutions for idealized twin-wall blade components subjected to cyclic thermal and centrifugal loading - Skamniotis, C; Cocks, ACF (Elsevier, 2022)
Double-wall transpiration cooling systems offer the potential for performance improvements over conventional single wall systems in aerospace applications. Here we idealise the geometry in terms of a constrained 2 bar system which allows the development of analytical expressions for the entire range of possible mechanical responses under out-of-phase thermomechanical loading. The application of Koiter's shakedown theorem along with equilibrium is a powerful strategy for identifying mechanisms by which the structure can incrementally collapse (ratchetting). We show that twin wall systems with zero mechanical loading can ratchet in the compressive direction when severe thermal mismatch occurs, and that ratchetting is replaced by reverse plasticity as the bar thickness difference increases. Mechanisms exist where plastic strains do not occur at the extremes of the loading cycle. The degradation of yield strength of Ni alloys with temperature modifies drastically the response, while additional creep induced ratchetting and creep failure processes are shown to occur at extreme temperatures within a cycle. Our solutions aim to provide physical insight into the response of double-wall transpiration cooled Ni-based turbine blades.